AS TENTATIVAS DE CRIMINALIZAÇÃO DAS ARTES DE CURAR EM IRATI E MALLET-PR - 1925-1949 - SENDERSKI, HENRIQUE ALEXANDRO (2021)
The present text is the result of a historical research, in criminal lawsuits, filed in the cities of Irati and Mallet-PR, comprising the time range from 1925 and 1949. The objective is analyzing the attempts to criminalize the faith healing works of the defendants, as well as their routinely practices on the lawsuits. The practices of healing are identified in the records as "illegal medicine", "faith healing", "popular medicine" and "charlatanism", among other terms that, in the context of the cases, reveal the attempt to disqualify medical knowledge and, criminalization, both the practices and their practitioners. Michel de Certeau's theoretical framework inspires the understanding of power relations, highlighting the conflicts and divergent interests that can be partially identified and understood from the sources. Legal and medical actions and resistance to the exercise of power correspond to strategies and tactics in a society that wants to modernize, discipline which needs to turn some characters into criminals.